Qualitative study on the evaluation of humanistic care quality in geriatric nursing based on three-dimensional quality structure theory - Yuan, Jinrong; Li, Ling; Zhan, Qin; Liu, Huijuan; Liu, Yilan; You, Yanjie (Frontiers in Medicine, 2025)
AimsTo understand the current situation of nursing humanistic care in geriatrics, to integrate the humanistic care quality evaluation viewpoints based on the Donabedian’s three-dimensional quality structure theory, and to provide a reference direction for constructing a nursing humanistic care quality evaluation system in geriatrics specialties.Methods4 geriatric nursing managers and 8 geriatric nurses of our hospital were selected for semi-structured interviews from October 2024 to December 2024, and based on the content analysis method, the data were analyzed and themes were refined using NVivo12 software.ResultsA total of 12 sub themes were extracted. The structural level: rationalization of human resources, caring hospital environment, system and responsibilities; Process level: caring communication, identifying individual needs, patient medication safety, prevention of high-risk patients, medical and nursing cooperation, and humanistic literacy of nursing personnel; Outcome level: satisfaction, patient outcomes, and incidence of adverse outcomes.ConclusionThe quality of geriatric nursing humanistic care is still room for improvement. We further optimize the structure of human resources by allocating psychiatric nurses and constructing a stratified nursing response mechanism to satisfy personalized humanistic care, and encourage the participation of family members to ensure the continuity of patient care, and ultimately improve the information-based nursing system to realize the full coverage of humanistic care and the transformation of geriatric nursing from “disease-oriented” to “whole-person care.”